Freedom of Learning: Lesson Learned from SALAM Community - Indri Ajeng Setyoningrum; Viena Rusmiati Hasanah; Sardin Sardin (STAI Hubbulwathan Duri, 2023)
The policy of the Freedom of Learning program by the Ministry of Education and Culture of the Republic of Indonesia is currently in the spotlight and special attention of education organizers and the academic community. Philosophically and conceptually, this has been implemented by the non-formal educational institution Sanggar Anak Alam (SALAM) Yogyakarta. The purpose of the study was to analyze the SALAM learning process and the roles of the facilitators concerning the Freedom of Learning policy. This study used a qualitative approach. Research informants were selected by snowball sampling technique. The data collection process was carried out by in-depth interviews, field notes, and documentation studies. Data analysis used the Miles and Huberman model. Triangulation was used to strengthen arguments in explaining research phenomena. Based on data analysis, it is known that SALAM had its learning model. They had a Learning Cycle as the curriculum. It also indicated that the role of teachers in SALAM included; 1) designing the curriculum according to the needs of students; 2) implementing active learning; and 3) encouraging the SALAM learning community. It followed the ideal goals of the Freedom of Learning philosophy.